2013
DOI: 10.1063/1.4798280
|View full text |Cite
|
Sign up to set email alerts
|

Variable-temperature Raman spectroscopic study of the hydrogen sensing mechanism in Pt-WO3 nanowire film

Abstract: Two special properties of Pt coated WO3 (Pt-WO3) nanowire film for sensing hydrogen gas flow in air are reported in this paper, including the large relative resistance change (close to 100%) and the dependence of the millisecond-scale response time on operating temperature. A variable-temperature Raman spectroscopic system is applied to record the structural changes of WO3 nanowires in situ during the input of H2 gas at different operating temperatures. Furthermore, based on the experimental results, two combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Moreover, a 3 cm À 1 shift of WÀ O stretching vibrations (at 699, 796 cm À 1 ) was observed in the Raman spectra (Figure 4g), indicating a length change for the WÀ O bonds. [39,40] This might be contributed by the dissociated H that migrated to the WO 3 , most likely by a hydrogen spillover effect, [37,41,42] reducing W 6 + to W 5 + [43] (Figure 4e). Stronger absorption at 500-800 nm in the UV/ Vis diffuse reflectance spectra (Figure 4h) after hydrogenation is attributed to chemisorbed H. [25] The hydrogen transfer over Pt/WO 3 was also supported by the smaller optical band gap (E g ) (calculated via Tauc's formula) of hydrogenated Pt/WO 3 (ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a 3 cm À 1 shift of WÀ O stretching vibrations (at 699, 796 cm À 1 ) was observed in the Raman spectra (Figure 4g), indicating a length change for the WÀ O bonds. [39,40] This might be contributed by the dissociated H that migrated to the WO 3 , most likely by a hydrogen spillover effect, [37,41,42] reducing W 6 + to W 5 + [43] (Figure 4e). Stronger absorption at 500-800 nm in the UV/ Vis diffuse reflectance spectra (Figure 4h) after hydrogenation is attributed to chemisorbed H. [25] The hydrogen transfer over Pt/WO 3 was also supported by the smaller optical band gap (E g ) (calculated via Tauc's formula) of hydrogenated Pt/WO 3 (ca.…”
Section: Methodsmentioning
confidence: 99%
“…As inferred from the negligible H 2 binding capability of unloaded WO 3 compared to Pt/WO 3 (detected by H 2 À TPD, Figure S8), hydrogen dissociation predominantly took place on Pt sites, which is consistent with previous studies. [37][38][39] We next compared the XPS, Raman, and UV/Vis diffuse reflectance spectra of 2D Pt/WO 3 before and after the hydrogenation. It was found that the relative percentage of W 5 + increased from 17 % to 22 % after hydrogenation (see XPS results in Figure 4e and Table S4) and surface oxygen species were consumed (Figure 4f).…”
Section: Methodsmentioning
confidence: 99%
“…25 In parallel, in situ Raman spectroscopy can track the structural evolutions of sensing material during gas sensing. 26 1d,e). The small nanoparticle showed a lattice distance of 0.24 nm, corresponding to the (111) crystal plane of the metallic Ag (Figure 1f).…”
Section: ■ Introductionmentioning
confidence: 96%
“…Recently, tungsten trioxide (WO 3 ), which is one of the binary TMO materials, has attracted significant attention for application in ReRAM devices [11][12][13][14][15][16][17][18][19][20] . WO 3 is a n-type, wide-bandgap semiconductor with an electronic bandgap (E g ) reported between 2.6 and 3.2 eV depending upon the crystallinity [12], which could be tailored according to the requirements by controlling the size of the nanoparticles; it decreases with size due to the quantum confinement effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is an important electrochromic material being transparent for most part of the visible spectrum. Its optical transmittance can be modulated by the presence of reducing gases (N 2 ) [14], external electrical stimulus [15] and heat [16]. Furthermore, it could be utilized as a photocatalytic [17], thermoelectric [18,19], and even ferroelectric material in ε-WO 3 form [19].…”
Section: Introductionmentioning
confidence: 99%